Hypoalgesia associated with elevated resting blood pressure: evidence for endogenous opioid involvement - Bruehl, Stephen (2009)
This study used a placebo-controlled, between-subjects opioid blockade design to evaluate endogenous opioid involvement in the hypoalgesia associated with elevated resting blood pressure (BP) in 163 healthy individuals. Participants were randomly assigned to Drug condition (placebo, naltrexone) and Task Order (computerized maze task with harassment followed by an ischemic pain task or vice versa). Resting BP was assessed, followed by drug administration, and then the pain and maze tasks. A significant Drug × Systolic BP (SBP) interaction was observed on McGill Pain Questionnaire-Affective pain ratings (P < .01), indicating that BP-related hypoalgesia observed under placebo was absent under opioid blockade. A significant Gender × Drug × SBP × Task Order interaction was observed for VAS pain intensity (P < .02). Examination of simple effects comprising this interaction suggested that BP-related hypoalgesia occurred only in male participants who experienced the pain task in the absence of emotional arousal, and indicated that this hypoalgesia occurred under placebo but not under opioid-blockade. Results suggest that under some circumstance, BP-related hypoalgesia may have an endogenous opioid-mediated component in healthy individuals, particularly men.